LOVE TOPIC IN UTKIR HASHIMOV'S STORIES (Archive of Conferences, 2021)
Demanding writer Utkir Hoshimov's bees cover not only acute socio-political issues and nationalspiritual views, but also topics about love. Through his many stories about love, such as "Long Nights", "Captive in Dreams", "Happiness", "Love", "Sale of Life", the artist will tell his book lovers about the magic of love, suffering, bitter past and unforgettable memories. 'has been a mystery. In this article, we summarize the pure love of the author's stories, which is full of emotions.